PENGARUH DAUR HIDUP, KINERJA, DAN KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL - Dini Kusumastuti (UNIVERSITAS KARIMUN, 2023)
Capital structure is one of the important decisions taken by a company's financial manager because capital structure decisions determine the overall cost of capital of a company. One important factor for the success of a business is in determining the company's capital structure. This study aims to examine the effect of life cycle, performance, and company characteristics on capital structure decisions in mining companies in Indonesia. The variables used in this study include life cycle (DH1, DH2, DH3), profitability, liquidity, asset structure as independent variables, and capital structure as the dependent variable. The sample used in this study is mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. Obtained 47 companies as research samples using purposive sampling method obtained 181 company data. This study uses multiple linear regression analysis using the SPSS 25 application to analyze the data. The results showed that the company's life cycle and asset structure have no significant effect on capital structure. Meanwhile, profitability and liquidity have a significant negative effect on the capital structure of mining companies listed on the Indonesia Stock Exchange in 2017-2021.